Research of Gravity Compensation Mechanism based on Non-circular Gear - Yang Yandong; Li Xinliang; Hou Yulei; Zeng Daxing (Jixie chuandong)
At present,most robots need to consume a large amount of energy to overcome their own gravity during operation. In order to reduce energy consumption and improve robot performance,a gravity compensation mechanism（ GCM） for a rotating joint manipulator is proposed. A non-circular gear planetary gear and torsion spring are used in the device,the gravity compensation of arbitrarily reachable working space of the manipulator can be realized,the static balancing mechanical model of the manipulator is established,the non-circular gear planetary gear train is designed according to the static balance constraint condition,and the transmission ratio distribution of non-circular gear planetary gear train is discussed. The simplest gear train that satisfied the moment balance is obtained. The design and analysis of the 2R parallel four-bar mechanism manipulator is carried out and imported into ADAMS for verification. The simulation results show that the driving torque is effectively reduced.